Cultivo sustentável de Gliricidia sepium em sistema de agricultura biossalina - Freitas, Douglas de Souza Souto (2020)
There is renewed interest among researchers and breeders in crops with resistance or tolerance to salinity and drought. The gliricidia features edible material, leaves and branches, which can be kept in the form of hay. In this way, it was aimed to analyze the agronomic characteristics of the culture of the gliricidia in different types of use submitted to irrigation with brackish water in drip system, with or without the effluent from fish farms, as well as determine the duration time of the different types of cut of the gliricidia to reach the point of hay. It was adopted a fully randomized experimental design with four replications in a split plot composed of two types of irrigation: brackish water from underground wells with or without the fish farming wastewater, and the split with a water depth of 75 mm per plant, represented by three types of cut of Gliricídia, whole plant (WP), herbaceous part (HP) and leaves. The variables evaluated were: the content of MS, production of green matter (PGM) and dry matter production (DMP), plant height (PH), stem diameter (SD), number of leaves (NL) and number of branches. The data of the agronomic characteristics were submitted to analysis of variance (ANOVA) using the SISVAR program 5.0, using the Tukey test at 5% probability. The treatment with brackish water with effluent from fish farms presented higher (P<0.05) plant height compared with the irrigation with brackish water. There was a higher (P <0.05) dry matter production (PMS) of the entire plant irrigated with fish farming effluents (14,742 kg / ha) compared to brackish water (9,655 kg / ha). The leaves did not complete the baling point (around 85% DM) in 48 hours, while the whole plant and the herbaceous part, according to the regression analysis, reached the hay point 38 and 39 hours after the exposure. The gliricidia shows growth and yield radish when irrigated with salt water, the effluent from aquaculture provides increments in the production of green matter and dry for cutting the entire plant. The gliricidia reaches point of hay from the whole plant with 40 hours and leaves with 48 hours.